KEPENTINGAN TIONGKOK DALAM KONFLIK DI AFGHANISTAN 2013-2017 - Rafqi Syawali; Faisyal Rani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research  is a political study which describes the interest of Tiongkok  in Afghanistan conflict. This research will focus on what made Tiongkok joint in Afghanistan conflict. This study interesting because describe about Tiongkok  interest in the conflict in Afghanistan is to maintain the security of the sovereignty and economic stability. This is qualitative research which used descriptive methods, and collecting datas from some resources like books, journals, official publications and relevant websites. This paper used the realism perspective and National Interest from Donald E. Nuechterlein. The object in this research is Tiongkok as main actor in International Relations. The result of this research shows that Tiongkok made some movement to save their economy, security and status in international community. Tiongkok come to Afghanistan made millitary base on that to help Afghanistan Government againts Taliban. Tiongkok also made international economic organizaitation to help economic Asia country.Keywords : Interest, Conflict, Politic, Security, Talibans